ARUGULA FARMING WITH INFLUENCE OF EXTRACT OF LEAVES JATROPHA - TONDO, W. L.; GURGACZ, F.; SANTOS, R. F. (Revista Brasileira de Engenharia de Biossistemas, 2013)
Arugula (Eruca sativa L.) is an essential vegetable in the diet of a large part of the population, especially for their nutritional composition with high content of potassium, sulfur, iron and vitamins A and C. This work on the influence of the aqueous extract of leaves of jatropha cultivation of arugula. We used concentrations of extract of Jatropha to make the treatments and 0% (control), 5, 10, 20, 40, 80 and 100%, considering how pure extract 200g green leaves of Jatropha in one liter of water distilled. Seeds were sown in specific trays for seedlings of vegetables, we used a manual sprinkler system. With increasing concentration of the aqueous extract of leaves of Jatropha curcas showed a decreasing trend in the number of leaves, seedling height, root size, stem diameter and fresh weight, proving the allelopathic effect of leaf extract of Jatropha cultivation arugula.